Sorting droplets beyond the Rayleigh limit under acoustic-gravity forces: a theoretical approach - Thirisangu, Jeyapradhap; Subramani, Karthick (Frontiers in Acoustics, 2025)
The physics of droplets beyond the Rayleigh limit offers a novel acoustic sorting method that is fundamentally different from the techniques applied to sort droplets within the Rayleigh limit. Using this “acoustic sorting beyond Rayleigh limit” method, we theoretically demonstrate that by controlling the frequency (f) and acoustic energy density (Eac), smaller droplets can be suspended while larger ones settle against gravity, or larger droplets can be suspended while smaller ones settle. Intriguingly, this method also enables the suspension of intermediate-sized droplets, allowing both smaller and larger droplets to settle simultaneously. Furthermore, acoustic sorting is demonstrated for droplets of identical size but with varying interfacial tensions.